Communities Shaping Sustainable Cities. (June 2019) - Hořická, J
Abstract: The contribution introduces significance of local communities in global context of sustainable urban development. Since last decades, urban regeneration, redevelopment and improvements of stabilized localities has become the subject of attention, as the limits of land use and urban expansion has been understood and generally accepted. Recently, the role of community and citizens has been emphasized in international strategies, for instance UN 2030 Sustainable Development Goals (2015) or UNESCO Strategic Objectives of the World Heritage Convention, so called Five C's (the fifth C representing Community added in 2007). Bottom-up initiatives and community activities have become important in urban revitalization and regeneration. The contribution aims to describe the activities and roles of various stakeholders, based on analysis of application project in Prague, Czech Republic inspired with a project in Basel, Switzerland, and characteristics of the evolution process heading towards community activation, which is important for the integrated planning processes, involving an interdisciplinary team and active public participation.